Determination of radial electric field from Pfirsch–Schlüter flows in the HSX stellarator. (6th February 2017) - Kumar, S.T.A.; Talmadge, J.N.; Dobbins, T.J.; Anderson, F.S.B.; Likin, K.M.; Anderson, D.T.
Abstract: Inboard/outboard asymmetry in the impurity ion parallel flow is observed in the HSX stellarator using charge exchange recombination spectroscopy (CHERS). This observation shows the presence of counter-streaming Pfirsch–Schlüter flow predicted by neoclassical theory. The asymmetry of the flow is used to calculate the magnitude and direction of the radial electric field ( E r ), as well as the mean flow, using computed magnetic geometry factors. This method enables calculation of E r near the core of the HSX plasma where the E r obtained from the radial force balance equation has large uncertainties due to the relatively large width of the diagnostic neutral beam with respect to the plasma minor radius.